2021
DOI: 10.3390/medicina57111256
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder and Comorbid Use of Illicit Substances

Abstract: Substance use disorders (SUD) are highly prevalent in bipolar disorder (BD) and significantly affect clinical outcomes. Incidence and management of illicit drug use differ from alcohol use disorders, nicotine use of behavioral addictions. It is not yet clear why people with bipolar disorder are at higher risk of addictive disorders, but recent data suggest common neurobiological and genetic underpinnings and epigenetic alterations. In the absence of specific diagnostic instruments, the clinical interview is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 64 publications
1
14
0
7
Order By: Relevance
“…The present paper aimed to evaluate the factors associated with SUD and polySUD in a cohort of patients with BD. Evidence from epidemiological, clinical, and review studies has shown that the comorbidity between patients with a primary diagnosis of BD and SUD is frequent ( 23 , 27 , 28 , 35 ). This has also been confirmed in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present paper aimed to evaluate the factors associated with SUD and polySUD in a cohort of patients with BD. Evidence from epidemiological, clinical, and review studies has shown that the comorbidity between patients with a primary diagnosis of BD and SUD is frequent ( 23 , 27 , 28 , 35 ). This has also been confirmed in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons why patients with BD use illicit substances are different, including seeking relief by self-medication, improving psychic status, relieving tension and boredom, escaping from reality, achieving and/or maintaining elevated mood, and increasing energy ( 27 ). Furthermore, common genetic (i.e., polymorphism of the aldehyde hydrogenase and alcohol dehydrogenase, or 5HT 2C gene), socioeconomic, and environmental factors (i.e., access and availability of illicit drugs in the community, poverty), stressful events (i.e., trauma, physical, and sexual abuse), temperamental traits (i.e., a sensation of seeking behavior), lifetime suicide attempts, and psychiatric comorbidities (i.e., conduct disorder, cluster B personality disorder, and post-traumatic stress disorder) have been associated with SUD in patients with BD ( 24 , 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] A significant number of patients with bipolar disorder use drugs or alcohol instead of pharmacotherapy. Both depressed mood in depressive states and substance abuse are significantly associated with episodes of suicide attempts [28].…”
Section: Complications Of Untreated Bipolar Disordermentioning
confidence: 99%
“…However, more and more studies highlight cannabis as a risk factor and examine the relationship between the frequency of consumption, age of the consumer, and the onset or severity of bipolar disorder (Lalli, Brouillette, Kapczinski, & de Azevedo Cardoso, 2021). For opioids, alcohol, and drugs, prospective studies show that they increase the risk associated with bipolar disorder, without examining the specific differences (Preuss, Schaefer, Born, & Grunze, 2021).…”
Section: Life Eventsmentioning
confidence: 99%